2022
DOI: 10.3390/polym14101931
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Determination in Gastrointestinal Tracts of European Sea Bass (Dicentrarchus labrax) and Gilt-Head Sea Bream (Sparus aurata) from Tenerife (Canary Islands, Spain)

Abstract: Microplastic pollution has an extremely widespread distribution, to the extent that microplastics could be ingested by aquatic organisms, including species of commercial importance for fisheries and aquaculture. In this work, the anthropogenic particles content of the gastrointestinal tracts of 86 individuals of cultivated European sea bass (Dicentrarchus labrax, n = 45) and gilt-head sea bream (Sparus aurata, n = 41) from Tenerife (Canary Islands, Spain) was determined. Samples were bought at local markets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Our results confirmed that both seabass and seabream from off-shore aquaculture plants are subjected to contamination by plastics, even though the amount of particles detected was low. Comparing our results with the scientific literature, the number of items/individual detected is well below the study conducted by Sánchez-Almeida et al [23] and Kılıç [27] and lower also to the value obtained by Reinold et al [25] and Savoca et al [29]. Our study showed a similar percentage of incidence but a lower number of items/individual with respect to that of Bessa et al [26].…”
Section: Discussioncontrasting
confidence: 52%
“…Our results confirmed that both seabass and seabream from off-shore aquaculture plants are subjected to contamination by plastics, even though the amount of particles detected was low. Comparing our results with the scientific literature, the number of items/individual detected is well below the study conducted by Sánchez-Almeida et al [23] and Kılıç [27] and lower also to the value obtained by Reinold et al [25] and Savoca et al [29]. Our study showed a similar percentage of incidence but a lower number of items/individual with respect to that of Bessa et al [26].…”
Section: Discussioncontrasting
confidence: 52%
“…Despite the strict control measures, the introduction of microfibers in aquaculture systems cannot be avoided. Analyses of the gastrointestinal tracts of 86 samples of farmed European sea bass (Dicentrarchus labrax, n = 45) and gilt-head sea bream (S. aurata, n = 41) from Tenerife (Canary Islands, Spain) showed the high prevalence of microfibers (100% and 96.1%, respectively), most of which were cellulose microfibers together with polyester, polyacrylonitrile, and poly(etherurethane) [79]. Fishmeal has been investigated as a possible contamination source for farmed fish, showing an occurrence of about 124 microplastics per kg, including numerous microfibers (52.0 ± 14.0 items/kg), which may be derived from the contamination during the production process [80].…”
Section: Microfiber Contamination In Commercial Fishmentioning
confidence: 99%
“…10 (Swann-Morton-England) to remove the gastrointestinal tract from the top of the esophagus to the anus. The gastrointestinal tract was put into a bottle containing 10% KOH solution to digest biological material (Sanchez-Almeida et al, 2022). The gastrointestinal tract bottle was stored in an oven with a temperature of about 60 o C for 24 hours.…”
Section: Preparation Of Fishmentioning
confidence: 99%